Energy georesources and personnel training - A. A. Vercheba; A. E. Vorobyov (Известия высших учебных заведений: Геология и разведка)
Background. The dominant role of energy georesources in the mineral resources sector of Russian economy is considered. Achievements in this sector are determined by the quality of human capital. Successful implementation of the Strategy for the Development of the Mineral Resource Base of Russia until 2035 requires improved personnel training in the higher education system according to new educational programs in the disciplines of Applied Geology and Mining.Aim. Assessment of the current state of the mining and geological industry in Russia, as well as its methodological and technological basis as an objective indicator of the economic and social development of the social system.Materials and methods. Expert evaluation of the activities carried out by the Federal Subsoil Resources Management Agency in the direction of the geological study of energy resources.Results. The conducted analysis of the sustainability of the mineral resources sector in the era of globalization and Russia’s historical experience of creating the uranium industry shows the need to further develop the nuclear energy sector. This process requires modifications in the engineering geological education to revive Russian traditions of training specialists in the field of uranium mining and treatment.Conclusion. The prospects for increasing the mineral resources base of energy carriers and creating conditions for providing the country with energy raw materials should be supported by joint efforts of educational institutions and employers in the system of training geologists.